2010
DOI: 10.4102/sajr.v14i4.454
|View full text |Cite
|
Sign up to set email alerts
|

Beware the bifid rib!

Abstract: A 4-year-old girl was referred to Tygerberg Academic Hospital with a long-standing history of an asymptomatic anterior chest wall 'lump' . On physical examination, a bony mass was palpated in relation to the anterior aspect of the left 4th rib. Plain radiography demonstrated anterior widening of the left 4th rib (Fig. 1). Fearing a sinister cause, a multidetector computed tomography (MDCT) examination of the chest, with 3D reconstruction and volume rendering, was performed (Fig. 2). A congenital bifid left 4th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…But may present as a lump in anterior chest wall. 10 Anomalies of ribs may represent as an early indicator of other systemic diseases. It can be a feature of Gorlin -Goltz syndrome, a multisystem disorder that manifest with multiple Nevoid basal cell carcinoma, jaw cysts, congenital skeletal abnormalities such as bifid, splayed or synostotic ribs.…”
Section: Resultsmentioning
confidence: 99%
“…But may present as a lump in anterior chest wall. 10 Anomalies of ribs may represent as an early indicator of other systemic diseases. It can be a feature of Gorlin -Goltz syndrome, a multisystem disorder that manifest with multiple Nevoid basal cell carcinoma, jaw cysts, congenital skeletal abnormalities such as bifid, splayed or synostotic ribs.…”
Section: Resultsmentioning
confidence: 99%
“…[1,20] Other studies have identified additional diseases/malformations that can be associated with bifid rib specifically: deficient lateral clavicle, mandibular hypoplasia, macrocephaly, mental retardation, chest wall tumor, and costal fracture. [4,24] Unlike other rib anomalies, bifid rib usually occurs in the absence of vertebral defects. [1] Considering mesodermal origins of the ribs, it is sensible that costal abnormalities are often associated with defects in organs of mesodermal origin such as the heart and kidney.…”
Section: Symptoms Complications and Case Studiesmentioning
confidence: 99%